2022
DOI: 10.1021/acs.jmedchem.2c00085
|View full text |Cite
|
Sign up to set email alerts
|

Piezo-Type Mechanosensitive Ion Channel Component 1 (Piezo1): A Promising Therapeutic Target and Its Modulators

Abstract: Piezo1 is a member of the mechanosensitive piezo ion channel family, which transduces various mechanical stimulations into electrochemical signals. Piezo1 is closely implicated in different physiological processes ranging from erythrocyte volume homeostasis to lymphatic vessel formation and bone homeostasis. Aberrant Piezo1 functions caused by gain-of-function or loss-of-function mutations are associated with various pathological conditions. Due to the significant contribution on the recognition of Piezo ion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 116 publications
3
28
0
Order By: Relevance
“…Removing two chlorine atoms on ring A reduces binding affinity ( 1a ), while adding a fluorine at meta-position slightly increase the binding affinity in the open state ( 2a ). These RBFE predicted SARs are in excellent agreement with the qualitative experimental observations 26, 40 .…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Removing two chlorine atoms on ring A reduces binding affinity ( 1a ), while adding a fluorine at meta-position slightly increase the binding affinity in the open state ( 2a ). These RBFE predicted SARs are in excellent agreement with the qualitative experimental observations 26, 40 .…”
Section: Resultssupporting
confidence: 85%
“…Removing two chlorine atoms on ring A reduces binding affinity (1a), while adding a fluorine at metaposition slightly increase the binding affinity in the open state (2a). These RBFE predicted SARs are in excellent agreement with the qualitative experimental observations 26,40 . In addition to ABFE and RBFE approaches, we seek to validate Yoda1 binding site using an orthogonal approach that does not require prior knowledge of the binding site.…”
Section: Relative Binding Free Energy (Rbfesupporting
confidence: 85%
See 1 more Smart Citation
“…The mechanisms of ultrasound neuromodulation have been extensively studied but not fully understood where ultrasound, as a mechanical pressure can act on mechanosensitive ion channels, has attracted much attention (31). Piezo is a mechanically sensitive ion channel that contains two isoforms, Piezo1 and Piezo2, of which Piezo1, is widely expressed in the central nervous system (32)(33)(34). Recent studies have found that ultrasound can act on Piezo1, and the activation of Piezo1 can lead to the in ux of cations like Ca 2+ , regulating downstream signaling pathways (35,36).…”
Section: Introductionmentioning
confidence: 99%
“…However, to this date, none of the drugs that target mechanosensitive channels have passed through the full clinical trial gauntlet and received FDA approval. The recent discovery of the key role that mechanosensitive Piezo channels play in various mammalian cells has raised additional excitement [ 66 ], but no new drug candidates have yet emerged. The finding that Notch, a membrane bound intercellular signaling molecule that plays a central role in differentiation and cell fate determination is also activated by mechanical forces at the cell surface [ 67 ] opens another interesting path for therapeutics development, although this has not yet been explored either.…”
Section: Mechanobiology and Mechanotherapeuticsmentioning
confidence: 99%